STATUS KUALITAS AIR SUNGAI WOSI, KABUPATEN MANOKWARI PROVINSI PAPUA BARAT - Mayzarah, Erikha Maurizka; Sauyas, Jou Roni Demetrius; Alzair, Nur (UNIVERSITAS NEGERI MAKASSAR, 2024)
River water is a type of surface water that is usually used for community water needs. This research was conducted from October 2023 to May 2024 in the Wosi River, Wosi Village, Manokwari Regency. The parameters used in this research are TDS, pH, DO, BOD5, COD, Sulfate, Ammonia and Chloride. The method used is the pollution index. The results of this research are that the calculation results show an index value of 0.63 at the upstream of the river and 1.40 at the downstream. Based on the pollution index value, the upstream river is classified as having good water quality, while the downstream river has lightly polluted river water quality. Suggestions that can be conveyed from this research are the need to increase technical and non-technical efforts by the government and community in reducing and controlling Wosi river water pollution.